Tarnished heroes, charming villains, and modern monsters : science fiction in shades of gray on 21st century television - Porter, Lynnette (Mcfarland Books, 2010)
"In the series Heroes, Lost, Battlestar Galactica, Caprica, Doctor Who, and Torchwood, as well as Joss Whedon's many series, traditional heroes give way to "gray" heroes who must become more like the villains that they face in order to save society. This book examines heroes and villains, focusing on characters' perspectives on morality and their roles within society